2008
DOI: 10.1016/j.jasms.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Ion trap collision-induced dissociation of multiply deprotonated RNA: c/y-ions versus (a-B)/w-ions

Abstract: The dissociation of model RNA anions has been studied as a function of anion charge state and excitation amplitude using ion trap collisional activation. Similar to DNA anions, the precursor ion charge state of an RNA anion plays an important role in directing the preferred dissociation channels. Generally, the complementary c/y-ions from 5= P-O bond cleavage dominate at low to intermediate charge states, while other backbone cleavages appear to a limited extent but increase in number and relative abundance at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 29 publications
11
106
0
2
Order By: Relevance
“…The product ion spectrum of the quadruply charged precursor provides limited sequence information. This observation is in agreement with the data by McLuckey and coworkers [30], who found that low charge-states and low excitation amplitudes favor cleavage of the 5′-C-O bond of RNA, which results in c/y-ion pairs, whereas high precursor charge states trigger few dissociation channels only, resulting in restricted sequence coverage.…”
Section: Fragmentation Of 2′-o-methyl Oligoribonucleotidessupporting
confidence: 93%
See 1 more Smart Citation
“…The product ion spectrum of the quadruply charged precursor provides limited sequence information. This observation is in agreement with the data by McLuckey and coworkers [30], who found that low charge-states and low excitation amplitudes favor cleavage of the 5′-C-O bond of RNA, which results in c/y-ion pairs, whereas high precursor charge states trigger few dissociation channels only, resulting in restricted sequence coverage.…”
Section: Fragmentation Of 2′-o-methyl Oligoribonucleotidessupporting
confidence: 93%
“…Such behavior was observed in negative as well as positive ion mode. Furthermore, in negative ion mode, the precursor charge state of RNA has been shown to influence fragmentation [30]. Lower charge states were found to maximize sequence coverage, whereas higher charge states favor charged base loss and promote specific dissociation channels.…”
Section: Introductionmentioning
confidence: 99%
“…As has been reported previously, the dissociation of oligonucleotide anions can be highly sensitive to precursor ion charge state [43][44][45]. To investigate the dissociation behavior of the LNA mixmer anions of higher charge states, the [M Ϫ 7H] 7-ions were isolated and subjected to ion trap CID.…”
Section: Ion Trap Collision-induced Dissociation Of Functional Lna-dnmentioning
confidence: 99%
“…In the past few decades, continuous efforts have been devoted to the investigation of the dissociation reactions of charged compounds derived from protonation [4][5][6][7][8] or deprotonation [9][10][11][12][13]. On the other hand, the mass spectrometric fragmentations of metal cationized, especially lithiated biomolecules, have attracted much attention because of the desire to measure intrinsic metal ion affinity and identify the binding sites [14,15], and because the interesting dissociation pathways exhibited by these compounds are usually different from the protonated and deprotonated analogues [16,17].…”
mentioning
confidence: 99%